Significant weakening of Brewer‐Dobson circulation trends over the 21st century as a consequence of the Montreal Protocol - Polvani, Lorenzo M.; Ábalos Álvarez, Marta; Garcia, Rolando; Kinnison, Doug; Randel, William J. (Geophysical Research Letters, 2018)
Atmospheric Composition Modeling and Analysis Program (ACMAP) NASA. The data used in the study are available via the Climate Change Modelling Information (CCMI) project. (EU) Itiswellestablished that increasing greenhouse gases, notably CO2, will cause an acceleration of the stratospheric Brewer-Dobson circulation (BDC) by the end of this century. We here present compelling newevidence that ozone depleting substances are also key drivers of BDC trends. We do so by analyzing and contrasting small ensembles of “single-forcing” integrations with a stratosphere resolving atmospheric model with interactive chemistry, coupled to fully interactive ocean, land, and sea ice components. First, confirming previous work, we show that increasing concentrations of ozone depleting substances have contributed a large fraction of the BDC trends in the late twentieth century. Second, we show that the phasing out of ozone depleting substances in coming decades—as a consequence of the Montreal Protocol—will cause a considerable reduction in BDC trends until the ozone hole is completely healed, toward the end of the 21st century. National Science Foundation (US) National Aeronautics and Space Administration (US) Comunidad de Madrid Department of Energy (US) Depto. de Física de la Tierra y Astrofísica Fac. de Ciencias Físicas TRUE pub